ASPEK KELEMBAGAAN TERHADAP PENYELESAIAN PERKARA PERCERAIAN AKIBAT KEKERASAN DALAM RUMAH TANGGA (KDRT) DI PENGADILAN AGAMA ARSO - Musrifah (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2023)
This article discusses the results of research related to cases of domestic violence in the Arso Religious Court, the causes of which include physical violence, economic violence, psychological violence, sexual violence, and spiritual violence. This research was conducted to find out the causes and resolution of cases of domestic violence that resulted in divorce. This research was conducted for 2 months (June-August 2022) with the research location in Keerom Regency (Arso Religious Court). The results of the study explain that the form of Divorce Case Settlement Due to Domestic Violence in the Arso Religious Court is by advising through trials or mediation outside the court and if the peace process does not succeed in reaching an agreement between the two parties, then the process of examining the case is continued in court using the principle of personality to-th Islam, the principle of freedom, the principle of the obligation to reconcile, the simple principle of fast and low cost, the principle of closed court hearings for certain cases, and the principle of equality before the law. As for the legal consequences for victims of domestic violence at the Arso Religious Court, namely that the plaintiff may sue/ sue for their rights post-divorce, namely past income, iddah maintenance, mut'ah, child custody, child maintenance and other assets.